Challenges and Strategies for Hypertension Control in the Young Generation in Indonesia: A Bibliometric Review - Solihah, Gina Maratus; Prijatmoko, Dwi; Luthviatin, Novia (citeus, 2025)
Hypertension among young people in Indonesia has become an increasingly alarming public health problem due to lifestyle changes, low awareness, and limited access to preventive health services. This review aims to analyze the challenges and strategies for controlling hypertension in young populations based on national and international literature, supported by bibliometric analysis. Data were obtained from the Web of Science (WOS) database and analyzed using VOSviewer to map research trends, keyword relationships, and collaboration networks related to hypertension in youth. The 2018 Riskesdas data showed that 34.1% of Indonesian adults aged ≥18 years had hypertension, with major risk factors including obesity, excessive salt intake, and lack of physical activity. Despite extensive healthcare coverage, blood pressure control remains inadequate. Globally, Indonesia’s prevalence mirrors developing countries such as China, India, and Nigeria, driven by unhealthy urban lifestyles and poor treatment adherence. Key challenges in managing hypertension among adolescents include low awareness, misconceptions about antihypertensive therapy, limited healthcare access, and unhealthy habits such as poor sleep and irregular diet. Sociodemographic factors, psychological stress, and family history also increase vulnerability. To address these issues, comprehensive strategies are recommended, including early screening, community-based health education, lifestyle modification, and integration of national and international initiatives such as Posbindu and WHO’s HEARTS program. Strengthening health promotion from adolescence, improving blood pressure monitoring, and optimizing follow-up systems at primary care level are essential for long-term control. This review concludes that a multidisciplinary and youth-centered approach, supported by bibliometric insights, is vital to prevent hypertension and its complications among Indonesia’s young population.